Description of Electrogena sartorii sp. nov., a new representative of the genus Electrogena Zurwerra & Tomka, 1985 (Ephemeroptera: Heptageniidae), from Iran using molecular and morphological data - Moazzen, Mina; Keikhosravi, Alireza; Rastegar-Pouyani, Eskandar (Zootaxa, 2021)
A new species, Electrogena sartorii sp. nov., is described at the larval stage using molecular and morphological data from Iran. In addition, two species; Electrogena gibedede Sroka & Godunko, 2012 and Anapos kugleri (Demoulin, 1973) are recorded from Iran for the first time. Considering the fact that many areas in Iran are not well explored an urgent and complete survey, in particular on the order Ephemeroptera, is needed to uncover the real biodiversity.